Union Organizing Activity, Firm Growth, and the Business Cycle - Bronars, Stephen G.; Deere, Donald R. (American Economic Review, 1993)
This paper analyzes the relationship between changes in unionization and firm growth. Average growth is significantly lower in manufacturing firms that experience successful union elections, but these strong "effects" are largely illusory. We find no evidence of a significant relationship between unionization and firm growth, despite a strong cyclical pattern in election activity. Our results suggest that the significant negative effect of organizing activity on a firm's market value is not accompanied by any growth changes. We therefore cannot reject the hypothesis that the equity losses from union election activity represent a simple transfer of wealth from shareholders to workers.